Indirect taxation, public pricing and price cap regulation: A synthesis - Edilio Valentini (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
This paper provides a unified vision of a number of results that appeared in three separate streams of literature. The author emphasizes the strong parallelism between the results obtained in a number of papers that analyzed the relationships between price cap regulation, welfare maximization, welfare improvements, distributional preferences and poverty reduction and those originating from the well-established theories of optimal indirect taxation and tax reforms, as well as public pricing.
Keywords: D6; L5; 330; Price cap regulation; indirect taxation; public pricing